An update on health literacy dimensions: An umbrella review - Craig Smith; Stephen Behan; Sarahjane Belton; Catherine Nicholl; Maeve Murray; Hannah Goss (PLoS ONE, 2025)
Awareness of the value of health literacy has grown significantly in recent years, with the concept increasingly integrated within public health policy, research and practice, and notably, more commonly being explored in a systems approach to health promotion. The concept does however appear to be constantly evolving, with various iterations of definitions being used. As such, there is a need to review and update understanding of health literacy’s core components. This umbrella review aims to provide a contemporary understanding of health literacy and its dimensions. Searches were conducted between July and August 2023 across three databases, and 784 studies were identified and screened, with nine systematic reviews identified for extraction. All included systematic review articles aimed to conceptualise or define health literacy. Following a quality assessment, using the AMSTAR-2, inductive analysis was carried out to map specific health literacy dimensions identified in each included study to previously identified health literacy clusters. The findings of this umbrella review highlight the ever-evolving nature of the concept of health literacy; the responsibility placed on the individual to develop and maintain adequate health literacy. Despite the relatively poor reporting quality of many of the review articles included, the findings from this umbrella review point to the difficulty in developing tools to comprehensively measure health literacy, and critically, how to effectively improve health literacy at both an individual and populational level.